Impact of COVID-19 on the Changing Patterns of Respiratory Syncytial Virus Infections - Ishan Garg; Rahul Shekhar; Abu Baker Sheikh; Suman Pal (MDPI AG, 2022)
Seasonal epidemics of respiratory syncytial virus (RSV) is one of the leading causes of hospitalization and mortality among children. Preventive measures implemented to reduce the spread of SARS-CoV-2, including facemasks, stay-at-home orders, closure of schools and local-national borders, and hand hygiene, may have also prevented the transmission of RSV and influenza. However, with the easing of COVID-19 imposed restrictions, many regions are noticing a delayed RSV outbreak. Some of these regions have also noted an increase in severity of these delayed RSV outbreaks partly due to a lack of protective immunity in the community following a lack of exposure from the previous season. Lessons learned from the COVID-19 pandemic can be implemented for controlling RSV outbreaks, including: (1) measures to reduce the spread, (2) effective vaccine development, and (3) genomic surveillance tools and computational modeling to predict the timing and severity of RSV outbreaks. These measures can help reduce the severity and prepare the health care system to deal with future RSV outbreaks by appropriate and timely allocation of health care resources.